Astrocytes modulate sensory-evoked neuronal network activity - Justin Lines; Eduardo D. Martin; Paulo Kofuji; Juan Aguilar; Alfonso Araque (Nature Communications, 2020)
Astrocytes respond to neurotransmitters with calcium transients stimulating the release of gliotransmitters that regulate synaptic and neuronal functions. Here, the authors show that cortical astrocytes also respond to sensory inputs and regulate sensory-evoked neuronal network activity.